Analisis Perbandingan Penyelesaian Soal Matematika Tipe Hots Materi Bangun Ruang Gabungan - Wakit, Ahmat; Hasanah, Ummi Awwaliyah Af’idatul; Istiqomah, Istiqomah (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2024)
Many students are lazy to read HOTS (Higher Order Thinking Skills) type questions which are too complicated so that they increasingly do not understand the meaning of the question and this causes the quality of education, especially in learning mathematics in Indonesia to decline. This study aims to analyze students' errors in solving HOTS type problems in mathematics on combined geometry, especially cubes and blocks. The research method that the author uses is a qualitative descriptive research method. The data collection technique used in this research is a HOTS type of math problem test for combined cube and cuboid building materials, interviews and documentation. The results obtained are a comparison of values with an average of 40.61 from SDN 5 Karanggondang and 51.9 from MI Darul Huda 2 Karanggondang. At the C2 level question, namely solving, class 5 MI Darul Huda 2 students seem superior with 88% of students answering correctly. At the C4 level, namely analyzing there is no significant difference, namely 44% of the abilities of the fifth grade students of SDN 5 and 45% of the fifth grade students' abilities of MI Darul Huda. At the C5 level, namely concluding, comparing and assessing, it shows that the percentage of MI Darul Huda 2 students in correctly answering HOTS type math problems is greater than that of SDN 5 students.